Wilkins' clinical assessment in respiratory care - Heuer, Albert J. (St. Louis, Missouri : Elsevier, 2022)
Master the patient assessment skills you need to provide effective respiratory care! Wilkins' Clinical Assessment in Respiratory Care, 9th Edition prepares you to assist physicians in the decision-making process regarding treatment, evaluation of the treatment's effectiveness, and determining if changes in the treatment need to be made. Chapters are updated to reflect the latest standards of practice and the newest advances in technology. From lead author Dr. Albert Heuer, a well-known educator and clinician, this market-leading text also aligns content with National Board for Respiratory Care exam matrices to help you prepare for success on the NBRC's CRT and RRT credentialing exams. Comprehensive approach addresses all of the most important aspects and topics of assessment, so you can learn to assess patients effectively. Case studies provide real-life clinical scenarios challenging you to interpret data and make accurate patient assessments. Questions to Ask boxes identify the questions practitioners should ask patients (e.g., coughing, sputum, shortness of breath) or questions to ask themselves (e.g., lung sounds they are hearing, blood pressure, respiratory rate) when confronted with certain pathologies. Learning objectives, key terms, and chapter outlines begin each chapter and introduce the content to be mastered. Assessment questions in each chapter are aligned to the learning objectives and reflect the NBRC Exam format, with answers located on the Evolve companion website. Key Points at the end of each chapter emphasize the topics identified in the learning objectives, providing easy review. Simply Stated boxes highlight and summarize key points to help you understand important concepts.
Preparing for the patient encounter -- The medical history and the interview -- Cardiopulmonary symptoms -- Vital signs -- Fundamentals of physical examination -- Neurologic assessment of the respiratory patient -- Clinical laboratory studies -- Interpretation of blood gases -- Pulmonary function testing -- Chest imaging -- Interpretation of the electrocardiogram -- Assessment of the neonatal and pediatric patient -- Assessment of the older patient -- Respiratory monitoring in the intensive care unit -- Assessment of hemodynamic pressures -- Assessment of cardiac output -- Flexible fiberoptic bronchoscopy -- Nutrition assessment of patients with respiratory disease -- Assessment of sleep and breathing -- Assessment of the home care patient -- Documentation of the patient assessment.
Includes bibliographical references and index.
Keywords: Respiratory insufficiency -- Diagnosis; Respiratory therapists; Cardiopulmonary system -- Diseases -- Diagnosis; Physical Examination; Fulltext; Internet Resources